A Quality Improvement Curriculum for Internal Medicine Residents - Darcy Reed; Christopher Wittich; Monica Drefahl; Furman McDonald (Association of American Medical Colleges, 2009)
Abstract Introduction All residents graduating from ACGME-accredited programs must demonstrate competence in practice-based learning and improvement (PBLI) and systems-based practice (SBP). The principles and practice of quality improvement (QI) is a core component of these two competencies. We developed a 3-year, longitudinal QI curriculum to increase internal medicine residents' competency in PBLI and SBP, as well as to improve patient care through resident-led QI projects. To create the curriculum, we used an established, scholarly approach to curriculum development in medical education. We also developed multiple methods for learner assessment and curriculum evaluation. Methods This resource includes a comprehensive users' guide with background and rationale, all materials needed to teach the curriculum including step-by-step guides to modules with hand-outs and references, learner assessment, curriculum evaluation information, and detailed instructions for faculty. The curriculum takes place over the 3 years of residency. During this time residents are exposed to modules that introduce the concepts of QI, and complete a QI project under faculty guidance. Results Summative assessment of QI competency is performed using the QIPAT-7, a seven-item instrument used to numerically assess the quality of residents' written QI proposals. Each of the seven items is scored using an ordinal 5-point scale where 1 = Needs Improvement, 3 = Meets Expectations, and 5 = Exceeds Expectations. The 145 residents who have completed the curriculum have received a mean QIPAT-7 score of 3.31 (SD = 0.69). Discussion We found that by identifying opportunities for residents to present and publish their QI projects, we achieved more enthusiastic resident participation in the curriculum. We also learned the importance of identifying an appropriate project mentor for residents and the importance of identifying qualified mentors at our institution (including those with formal QI credentials) and inviting them to mentor residents. We continue to work on developing mechanisms to link residents with appropriate mentors within our large institution. A third lesson we discovered is the benefit of aligning residents' QI projects with institutional priorities and initiatives. In our experience, it is easier to obtain institutional support for residents' QI initiatives when the focus of the project is related to important institutional activities.